Can we win the war on obesity with pharmacotherapy?. Issue 10 (2nd October 2016) - Gotthardt, Juliet D.; Bello, Nicholas T.
ABSTRACT: Introduction : Obesity is a major health concern for several countries. The United States (U.S.) has arguably led the world in the percentage of overweight and/or obese per capita for several decades. As a result, numerous FDA-approved pharmacotherapeutic options are available for the long-term treatment of obesity. Although most of these medications have been on the U.S. market for a few years and have demonstrated efficacy for long-term weight loss in clinical trials, the impact of these medications on obesity in the U.S. has yet to be realized. Areas covered : We will review and evaluate why pharmacotherapy for obesity has not produced a meaningful reduction in the number of overweight and obese adults in the U.S. Expert commentary : Several obstacles, such as adverse drug effects, poor insurance coverage, not treating obesity as a chronic disease, and availability of other weight loss alternatives, has resulted in poor performance of pharmacotherapy for obesity in the U.S. market.